What is Good? A Study of Educational Insights in Nicomachean Ethics (Book I, II and III). (January 2022) - Bardapurkar, Abhijeet
This work is a study of Aristotle's Nicomachean Ethics (Book I, II and III) to characterize the good : the good that features in education and good life. Nicomachean Ethics teaches us that human good is neither in thought/theory, nor in action/practice alone, it is neither an exclusively individual prerogative, nor an outright social preserve. And, human good is impossible without education. The practice of education can neither be isolated nor conceptualized apart from the demands of human life. If education is for human well-being—for human good—the good then is not in action alone, but action in accordance with the excellence (or virtue) 1 of the actor. What unifies reason and action, knowing and doing is learning to be an excellent (or virtuous) person—a person who is well-disposed in her affections and action, whose judgements are true, and decisions correct; and whose intellect and character are in harmony with the human nature.